How reliable is µXRF core scanning at detecting tephra layers in sedimentary records? A case study using the Lake Suigetsu archive (central Japan). (9th May 2022) - McLean, Danielle; Albert, Paul G.; Schlolaut, Gordon; Lamb, Henry F.; Marshall, Michael H.; Brauer, Achim; Wade, Jon; Nakagawa, Takeshi; Smith, Victoria C.
Abstract: Here, we evaluate the ability of micro X‐ray fluorescence (µXRF) core scanning to identify non‐visible volcanic ash (cryptotephra) layers in sedimentary records. Its suitability is assessed using the annually resolved lacustrine sediments of Lake Suigetsu (Japan) for which there is high‐resolution ITRAX µXRF core scanning data, and a detailed crypto‐tephrostratigraphy (formerly established via density separation techniques). The studied core sections contain 10 visible and 30 cryptotephra markers that span a range of glass concentrations (from 1000 to >20 000 shards per gram of dried sediment) and compositions (basalts, trachy‐andesites, phonolites, trachytes and rhyolites), thus providing an ideal case study. The ITRAX core scanner produced recognisable µXRF elemental responses for the visible ash layers, including those just 1 mm thick. However, just 10% of the cryptotephra layers could be unequivocally identified. Although this study demonstrates that µXRF core scanning should not be used as an independent method within a similar geological setting, we show it can provide a powerful tool alongside traditional techniques. Where detected, µXRF profiles can verify and refine cryptotephra positions (here to a sub‐millimetre resolution), and help establish reworking signatures. These insights create possibilities for ultra‐precise synchronisation of records, improved chronological modelling and help generate more complete eruption histories.